ATP/P2X7 receptor signal aggravates ischemic stroke injury by activating Th17 cells via STAT3/IL-21 pathway - Liu, Wenying; Li, Denghui; Zhang, Mengjie; Yin, Jun; Wang, Peng; Liu, Paiyu; Song, Zhiqiang; Ni, Bing; Peng, Yanmeng (Frontiers in Immunology, 2025)
BackgroundDuring cerebral ischemia, adenosine triphosphate (ATP) is released into the extracellular matrix from damaged neurons and glial cells, functioning as a danger signal. However, the involvement of ATP/P2X7 signaling in regulating the infiltrated lymphocytes during ischemia-reperfusion (IR) injury remain unclear.MethodsThe expression level of P2X7 was evaluated in infiltrated lymphocytes from experimental stroke mice. To further elucidate the role of P2X7 signaling in infiltrated immune cells during ischemic stroke, P2X7-knockout (KO) mice and Rag2-/- mice were utilized. Additionally, in vitro experiments were conducted to explore the underlying mechanisms.ResultsFlow cytometry analysis revealed that the expression of P2X7 was mainly expressed in CD4+and CD8+T cells among the infiltrated lymphocytes in stroke lesions of the mice. P2X7-KO mice exhibited smaller infarct sizes and improved neurological function compared to wild-type mice. Rag2-/- mice that received P2X7-KO CD4+T cells demonstrated reduced ischemic-reperfusion injury and a decreased level of IL-17A and frequency of Th17 cells compared to Rag2-/- mice that received wild type CD4+T cells. Transcriptome sequencing and in vitro experiments indicate that P2X7 may mediate the expression of IL-21 and regulating the synthesis of IL-17A and the differentiation of Th17 cells. We also confirmed that P2X7 receptor regulates IL-21 through STAT3 signaling.ConclusionsOur findings suggest that the loss of ATP/P2X7 signaling in CD4+T cells may inhibit the pSTAT3, IL-21 pathway, leading to reduced differentiation of Th17 cells and ultimately mitigating IR injury. This provides novel insights into the role of ATP/P2X7-mediated signaling in T cell inflammation during ischemic stroke.